What Keeps Students from Driving under the Influence of Alcohol and Prescription Drugs?: the Impact of Legitimacy of the Law, Prudent Behaviour and Perceived Dangerousness - Machura, Stefan (Oñati Socio-Legal Series, 2019)
Driving under alcohol or while under the influence of a medication that impedes the ability to control a car are punishable offenses. The study asks if the perceived legitimacy of law, the perceived dangers of driving, including detection by the police, and the individual inclination to engage in risky and imprudent behaviour influence the likelihood of committing those offenses. At a British university, 337 students took part in a questionnaire study. The results show that students are less inclined to drive under alcohol than under medication. Both are variously influenced by practical circumstances like the frequency of driving, of drinking and the actual taking of such medication, even pressures to drive regardless. Driving under medication is also related to legitimacy of law. The difference may come from the absence of a public narrative for driving under medication: some students fall back to their attitude to the law.